Chromosomes and karyotype analysis of a liver fluke, Opisthorchis viverrini, by scanning electron microscopy - Worasak Kaewkong (2018)
Opisthorchis viverrini, a human liver fluke, has been categorized as the carcinogenic organism according to the strong association with carcinogenesis of cholangiocarcinoma (CCA). The infection of this food-borne parasite is a major impact on the health of humans, especially CCA patients in the northeast of Thailand. Taxonomy, morphology, epidemiology and molecular study of O. viverrini have been publicized increasingly but the precise karyotypic study is still incomplete. In this study, the chromosomes of O. viverrini were prepared from the testes of adult worms retrieved from metacercariae infected-hamsters. The chromosomes of O. viverrini were identified in haploid (n = 6) meiotic metaphase and in diploid (2n = 12) mitotic metaphase by light microscopy. The chromosome number, length and nomenclature of each chromosome were determined by scanning electron microscopy. The six chromosomes consist of one large-sized metacentric, one medium-sized metacentric, two small-sized metacentric, one small-sized submetacentric and one small-sized acrocentric chromosomes with the lengths of 2.84 ± 0.03, 2.12 ± 0.10, 1.71 ± 0.13, 1.44 ± 0.04, 1.23 ± 0.03 and 0.84 ± 0.13μm, respectively. This is the first karyotype analysis of O. viverrini with defined complete nomenclature. © 2012 Elsevier Ireland Ltd.